Chapter 10 Cancerous Contraceptives and the Incubation of Monsters A Quechua Reproductive Etiology and Producing Necro-Techno-Sapiens - Irons, Rebecca (Taylor & Francis, 2021)
Biomedical pharmaceuticals, and specifically hormonal contraceptives, are often framed as tools to help women gain control over their lives through planning future offspring and being granted the ability to pursue life projects free of child-rearing concerns. In reproduction, hormonal contraceptives are one such pharmaceutical that could potentially be framed as "biohacking" by "enhancing" humans and rendering them cyborgian by suppressing "unwanted" menstruation and its associated bodily troubles. This chapter is based on ethnographic research undertaken over one year in a rural Quechua community in the province of Ayacucho, in the Peruvian Andes. In the period 1996-2000, an estimated 300,000+ Indigenous women underwent enforced sterilization in Peru as part of the national family planning program; many women did not give their consent, nor understand the permanence of the procedure.